2020
DOI: 10.1111/are.14743
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation among the fourMegalobramaspecies inferred by X‐ray photography

Abstract: Morphological traits measurement still plays a key role in description, identification, classification and phylogenetics of species. However, the traditional morphological measurement method is inefficient and often destructive to the studied organism. In this study, we propose and test an X‐ray‐based technique for non‐destructive morphological studies of fish. We use this approach to attempt to discriminate four species from the genus Megalobrama on the basis of their morphometric and meristic traits. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In the detection of agricultural products, Zou, Sun, and Zhang (2015) performed quick detection of the volume and mass of watermelons using X‐rays. J. Chen, Guo, and Wang (2020) used X‐ray technology for morphological studies of fish. The results showed that X‐ray photography was a suitable method for nondestructive and accurate detection of morphological parameters in the genus Megalobrama.…”
Section: Introductionmentioning
confidence: 99%
“…In the detection of agricultural products, Zou, Sun, and Zhang (2015) performed quick detection of the volume and mass of watermelons using X‐rays. J. Chen, Guo, and Wang (2020) used X‐ray technology for morphological studies of fish. The results showed that X‐ray photography was a suitable method for nondestructive and accurate detection of morphological parameters in the genus Megalobrama.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, M . amblycephala is distinguished by the morphology of the upper orbital bone and oral fissure, and also the caudal peduncle depth/length ratio [ 2 ]. It is mainly distributed in large- and medium-sized lakes in the middle and lower branches of the Yangtze River [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly distributed in large- and medium-sized lakes in the middle and lower branches of the Yangtze River [ 3 ]. M. skolkovii differs from the other three species in the longer length of the first swim bladder [ 2 ]. It inhabits the Amur, Yangtze, Yellow, and Minjiang rivers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies categorized the four species mainly based on morphologic traits and geographic distribution. For instance, M. amblycephala is distinguished by the morphology of the upper orbital bone and oral fissure, and also the caudal peduncle depth/length ratio [2]. It is mainly distributed in large-and medium-sized lakes in the middle and lower branches of the Yangtze River [3].…”
Section: Introductionmentioning
confidence: 99%